KONSEP AKUNTANSI KEPERILAKUAN DARI ASPEK PSIKOLOGI DAN PSIKOLOGI SOSIAL - Sari, Depita; Anastasia, Dhita; Ferdiani, Adinda; Sapitri Gajah, Rahmi (Research in Accounting Journal (RAJ), 2022)
This research is entitled "The Concept of Behavioral Accounting from Aspects of Psychology and Social Psychology". This study aims to determine the concepts that exist in the area of psychology and social psychology and to find out how they are applied to the theoretical system of behavioral accounting. The research method is descriptive. The result of this research is that we are able to understand aspects of psychology and social psychology comprehensively.